PENGARUH INKLUSI KEUANGAN, LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP LEMBAGA KEUANGAN MIKRO (STUDI PADA PROGRAM PUPM DESA GEDANGROWO) - Mochamad Rizal Yulianto; Dyah Renita Setyaningayu; Wisnu Panggah Setiyono (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
The aim of this study is to determine the effect of financial inclusion, financial literacy and financial attitudes towards microfinance institutions (case study in the PUPM program in the Gedangrowo village). This study applies quantitative method. The data collection method was carried out by distributing questionnaires to 200 respondents, namely PUPM members in Gedangrowo village. The sampling technique used random sampling and data analysis techniques used linear regression using the SEM AMOS 24 program. The results of this study indicate that financial inclusion did not significantly influence this financial institution can be stated with the value of C.Rcount of (0.563) ˂CRtable (1.96) is significant (0.573) while financial literacy has a significant effect on microfinance institutions with the value of C.Rcount of (3.958) ˃ C.Rtable (1.96) is significance (0.000) and financial attitude significantly influences the microfinance institutions with the value of C.Rcount of (3.380) ˂ C.Rtable (1.96) and its significance of (0.000).